Out in the country : youth, media, and queer visibility in rural America - Gray, Mary L. (Intersections (New York, N.Y.), 2009)
Winner of the 2009 Ruth Benedict Prize for Outstanding Monograph from the Society of Lesbian and Gay Anthropologists Winner of the 2010 Distinguished Book Award from the American Sociological Association, Sociology of Sexualities Section Winner of the 2010 Congress Inaugural Qualitative Inquiry Book Award Honorable Mention From Wal-Mart drag parties to renegade Homemaker's Clubs, Out in the Country offers an unprecedented contemporary account of the lives of today's rural queer youth. Mary L. Gray maps out the experiences of young people living in small towns across rural Kentucky and along its desolate Appalachian borders, providing a fascinating and often surprising look at the contours of gay life beyond the big city. Gray illustrates that, against a backdrop of an increasingly impoverished and privatized rural America, LGBT youth and their allies visibly--and often vibrantly--work the boundaries of the public spaces available to them, whether in the high schools, publc libraries, town hall meetings, churches, or through websites.